Incidence of main viruses infecting local garlic in Java, Indonesia - Hidayat, Sri Hendrastuti; Meliyana; Refa Yulianingsih; Diny Dinarti; Sari Nurulita (Universitas Lampung, 2023)
Virus infection is one of the challenges in garlic production due to it perpetuates from one generation to the next and its infection caused huge yield reduction. There was still few information regarding virus status on Indonesian local garlic cultivars. This study was aimed to detect four major viruses infecting local garlic in Indonesia, they were members of genus Potyvirus (Onion yellow dwarf virus/OYDV, Leek yellow stripe virus/LYSV), and Carlavirus (Garlic common laten virus/ GCLV and Shallot latent virus/SLV). Garlic samples were obtained from IPB University collection and field survey in Tegal and Karanganyar (Central Java Province). Dot immuno-binding assay (DIBA) was done for initial virus indexing on non-commercial and commercial cultivars. Reverse transcription polymerase chain reaction (RT-PCR) using four specific primers was done to detect virus on commercial cultivars. DIBA from leaf samples showed that virus incidence of OYDV was relatively higher (92.3 to 100%) than GCLV and SLV (84.6 to 100%) from all tested cultivars. On average, ‘Lumbu Hijau’ has the lowest level of virus titter (severity) than other cultivars. The virus incidence of both bulbil and single clover was similar (97 – 100%) while virus titter of OYDV, GCLV, and SLV on bulbil was the lowest than other propagation materials. Detection by RT-PCR from two commercial cultivars showed that ‘Lumbu Hijau’ has less virus incidence than ‘Jawa Lama’. LYSV, OYDV, GCLV were detected on both cultivars but SLV was not found. Further virus indexing using larger number of samples and involving more virus targets needs to be done.